2010
DOI: 10.1128/aac.00834-10
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance in Acinetobacter baumannii Is Mediated by Complete Loss of Lipopolysaccharide Production

Abstract: Infections caused by multidrug-resistant (MDR) Gram-negative bacteria represent a major global health problem. Polymyxin antibiotics such as colistin have resurfaced as effective last-resort antimicrobials for use against MDR Gram-negative pathogens, including Acinetobacter baumannii. Here we show that A. baumannii can rapidly develop resistance to polymyxin antibiotics by complete loss of the initial binding target, the lipid A component of lipopolysaccharide (LPS), which has long been considered to be essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
663
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 690 publications
(736 citation statements)
references
References 38 publications
34
663
2
9
Order By: Relevance
“…baumannii [49]. Alterations in the lipid A biosynthesis genes (lpxA, lpxC, and lpxD) by amino acid substitutions, deletions, or insertion of ISAba1 are responsible for the loss of LPS [49,50].…”
Section: Colistin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…baumannii [49]. Alterations in the lipid A biosynthesis genes (lpxA, lpxC, and lpxD) by amino acid substitutions, deletions, or insertion of ISAba1 are responsible for the loss of LPS [49,50].…”
Section: Colistin Resistancementioning
confidence: 99%
“…Alterations in the lipid A biosynthesis genes (lpxA, lpxC, and lpxD) by amino acid substitutions, deletions, or insertion of ISAba1 are responsible for the loss of LPS [49,50]. A recent metabolomic study revealed that an LPS-deficient, colistin-resistant A. baumannii strain showed perturbation in specific amino acid and carbohydrate metabolites, particularly pentose phosphate pathway and TCA (tricarboxylic acid) cycle intermediates [37].…”
Section: Colistin Resistancementioning
confidence: 99%
“…Outbreaks of carbapenem associated multidrug resistant A. baumannii may be the most problematic issue to treat the infected patients since the only viable therapeutic option for this infection is polymyxins [9], but polymyxins cause neuro-and nephro-toxicity [27] and polymyxin selection pressure can readily develop polymyxin resistant A. baumannii [28] [29]. In this study, most of the isolates showed carbapenem associated multidrug resistance, which was similar as other areas of the United States and worldwide [9] [11] [30], and more sadly some of them conferred intermediate levels of polymyxin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies relevant to the antibiotic treatment of A. baumannii implicate the loss of LPS with colistin resistance (through mutations in genes involved in LPS synthesis) and with the two-component system PmrAB. 20,21 At the same time, certain isolates that are colistin resistant display marked loss of virulence. 22 Proteomic analysis demonstrate that the cost of colistin resistance involves, among others such as chaperones and metabolic enzymes, loss of outer membrane proteins.…”
Section: The Human Host and Virulencementioning
confidence: 99%